Implementasi Program Bimbngan dan Konseling - Kamil, Annas; Alizamar, Alizamar; Yusri, Yusri (Konselor, 2014)
Abstract: Basic tasks the teacher supervisor is compiling the program guidance and counseling, implement the program guidance and counseling, evaluate program implementation guidance and counseling, analysis of the results of the implementation of the guidance and counseling and follow-up program implementation guidance and counseling to learners who becomes his responsibility. In fact guidance and counseling teachers of government senior high schools in Solok Regency did not elaborate on the program guidance and counseling in accordance with the types of services and areas of development without any elaboration time allocation, class of service to be provided, the material will be presented and didn’t have the weekly program of guidance and counseling. This study used a descriptive approach. The population of the research is all of guidance and counseling teachers in government senior high schools in Solok Regency, totally 49 people with sampling techniques namely the sampling area of 32 people. Data collection techniques using question form. The Data were analyzed using percentage technique.